Qiangjing Tablets Regulate Apoptosis and Oxidative Stress via Keap/Nrf2 Pathway to Improve the Reproductive Function in Asthenospermia Rats - Li, Guangsen; Zhang, Peihai; You, Yaodong; Chen, Diang; Cai, Jian; Ma, Ziyang; Huang, Xiaopeng; Chang, Degui (Frontiers in Pharmacology, 2021)
Asthenozoospermia (AZS), is a common cause of male infertility. Currently, most drugs for azoospermia lack desirable therapeutic efficiency, therefore developing new drug therapy is important. Qiangjing tablets could enhance renal function and improve sperm quality. The purpose of this study was to examine whether Qiangjing tablets could improve the reproductive function in azoospermia rats through activating the Nrf2/ARE pathway, and how to regulate energy metabolism and oxidative stress in this process. Sperm motility, sperm concentration and sperm viability were detected by WLJY-9000 Weili Digital Color Sperm Quality Detection System. HE staining was used to observe the pathological condition of testis in AZS rats. Cell apoptosis was analyzed by Tunnel staining and flow cytometry. The changes of mitochondrial membrane potential were detected by JC-1. The levels of Estradiol, testosterone and luteinizing hormone, activity of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), and content of malondialdehyde (MDA) and glutathione (GSH) were detected by ELISA. The effects of Qiangjing Tablets on GC-1 spgs and Nrf2 protein were investigated through CCK-8 assay and western blot. The expression levels of HO-1, Keap1, and P-Nrf2 were detected by western blot. The results demonstrated that Qiangjing tablets upregulated levels of sperm motility, sperm concentration and sperm viability, which was shown to significantly increase levels of HO-1, Keap1, P-Nrf2, Estradiol and testosterone, along with increasing the activity of SOD, GSH-Px and GSH and suppressing the MDA content, luteinizing hormone and Vimentin level. Qiangjing tablets could significantly inhibit spermatogenic cells apoptosis and promote GC-1 spgs viability, increase PE/FITC ratio, mitochondrial membrane potential and reduc oxidative stress. Qiangjing tablets protected spermatogenic cell to upregulate male sex hormoneto, improved the sperm quality and reproductive function in AZS rats via activating the Keap/Nrf2 signaling pathway.